FIXED DOSE COMBINATION THERAPY IS ASSOCIATED WITH BETTER BLOOD PRESSURE CONTROL AND LOWER ALBUMINURIA IN REAL-LIFE COHORT DURING 7 YEARS OF FOLLOW UP. ENAH – CROATIAN RURAL STUDY. (June 2018) - Jelakovic, A.; Abramovic, M.; Dika, Z.; Domislovic, V.; Djapic, K.; Fucek, M.; Gelineo, L.; Josipovic, J.; Karanovic, S.; Kos, J.; Leko, N.; Matijevic, V.; et al.
Abstract : Objective: The aim of this study was to analyze differences in blood pressure (BP) control and albuminuria between subjects treated with fixed dose combination (FCD) and those treated with free components in real-life during the 7 years follow up period. Design and method: Out of 1134 subjects (door-to-door enrollment, participation rate 80%) data on 236 (54 men; 182 women; mena age 63.2 years) treated hypertensives (HT) were analyzed at the end of 7 years of follow-up. At enter 136 of them were already treated HT (group A) and 100 were new-diagnosed HT (group B) who had started with antihypertensive therapy from that moment. Local GP were allowed to tailor antihypertensive therapy during the follow up period. At basal and at the end of follow up BP was measured by physicians who were project collaborators (ESH/ESC guidelines; OmronM6); salt intake (spot urine - Kawasaki equation), eGFR (CKD-Epi) and albumin-to-creatinin ration (ACR mg/g;first morning urine sample) were analyzed in central lab. Pregnant women, terminal ill, bed-ridden patients, those with severe disability, mentally ill or suffering from dementia or at least one limb amputated/immobilized were exclided. Results: At the end of follow up BP controll was achieved in 31.6% and 38% of HT (group A and B, respectively). In both groups, there there were no significnat differences in salt intake, BMI, smoking and the number of used drugs between controlled and uncontrolled subjects (p < 0.05). However, in group A significant increase in FDC prescription was observed ih the controlled vs.uncontrolled subjects (22% vs. 5.5%). BP control was associated with lower ACR in group A (14.9 vs.76.3; p < 0.01) and group B (9.1 vs.24.9; p < 0.05). Conclusions: In this real-life cohort after 7 years of follow-up BP controll was ahived with more drugs but only if used as FDC what was associated with better organoprotection i.e.lower ACR. Overall poor BP control and organoprotection could be improved using more FDC.